2021
DOI: 10.3390/nu13051624
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chlorella pyrenoidosa Protein as a Source of Novel Angiotensin I-Converting Enzyme (ACE) and Dipeptidyl Peptidase-IV (DPP-IV) Inhibitory Peptides

Abstract: Chlorella pyrenoidosa (C. pyrenoidosa) is a microalgae species with a remarkably high protein content that may potentially become a source of hypotensive and hypoglycemic peptides. In this study, C. pyrenoidosa proteins were extracted and hydrolyzed overnight with pepsin and trypsin with final degrees of hydrolysis of 18.7% and 35.5%, respectively. By LC-MS/MS, 47 valid peptides were identified in the peptic hydrolysate (CP) and 66 in the tryptic one (CT). At the concentration of 1.0 mg/mL, CP and CT hydrolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…In this study, it was clearly demonstrated that both SH and PH maintain their ability to reduce the activity of both DPP-IV and ACE on Caco-2 cells, even though both hydrolysates are active at a concentration ranging between 0.1 and 5 mg/mL, indicating that SH and PH are less active in cell-based than in cell-free conditions, respectively. Similar results have been previously obtained on peptic and tryptic hydrolysates of spirulina and chlorella proteins, respectively [32,34,35]. Also, in those cases, it was observed that all the tested hydrolysates were more active in cell-free than in cell-based assays, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, it was clearly demonstrated that both SH and PH maintain their ability to reduce the activity of both DPP-IV and ACE on Caco-2 cells, even though both hydrolysates are active at a concentration ranging between 0.1 and 5 mg/mL, indicating that SH and PH are less active in cell-based than in cell-free conditions, respectively. Similar results have been previously obtained on peptic and tryptic hydrolysates of spirulina and chlorella proteins, respectively [32,34,35]. Also, in those cases, it was observed that all the tested hydrolysates were more active in cell-free than in cell-based assays, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…DPP-IV and ACE are important membrane peptidases which are physiological expressed by many tissues; i.e., intestine [30,31]. Indeed, human intestinal Caco-2 cells represent a reliable model which has been already developed and validated for the study of peptides with DPP-IV or ACE inhibitory properties [23,32,33]. In this study, it was clearly demonstrated that both SH and PH maintain their ability to reduce the activity of both DPP-IV and ACE on Caco-2 cells, even though both hydrolysates are active at a concentration ranging between 0.1 and 5 mg/mL, indicating that SH and PH are less active in cell-based than in cell-free conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, findings clearly demonstrated that FPH maintain their ability to reduce the DPP-IV activity on Caco-2 cells, even with less activity. Comparable findings have been already obtained on plant-derived hydrolysates [ 58 , 59 , 61 ]. Protein hydrolysates showed better activity in cell-free than cell-based assays, even in these cases.…”
Section: Discussionsupporting
confidence: 82%
“…In this context, DPP-IV is a relevant peptidase physiological expressed by many tissues, i.e., intestine [ 56 , 57 ]. Human intestinal Caco-2 cells are widely used for the study of peptides with DPP-IV inhibitory activity, as they represent a reliable and validated model [ 58 , 59 , 60 ]. In this study, findings clearly demonstrated that FPH maintain their ability to reduce the DPP-IV activity on Caco-2 cells, even with less activity.…”
Section: Discussionmentioning
confidence: 99%